The lost world of scripture : ancient literary culture and biblical authority - Walton, John H., 1952-; Sandy, D. Brent, 1947- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2013)
"From Dr. John H. Walton, author of the bestselling The Lost World of Genesis One, and Dr. D. Brent Sandy, author of Plowshares and Pruning Hooks, comes a detailed look at the origins of Scriptural authority in ancient oral cultures and how it informs our understanding of the Old and New Testaments today. Stemming from questions about Scriptural inerrancy, inspiration and oral transmission of ideas, The Lost World of Scripture examines the process by which the Bible has come to be what it is today. From the reasons why specific words were used to convey certain ideas to how oral tradition impacted the transmission of Biblical texts, the authors seek to uncover how these issues might affect our current doctrine on the authority of Scripture.'In this book we are exploring ways God chose to reveal his word in light of discoveries about ancient literary culture,' write Walton and Sandy. 'Our specific objective is to understand better how both the Old and New Testaments were spoken, written and passed on, especially with an eye to possible implications for the Bible's inspiration and authority'" -- Publisher description.
Part 1. The Old Testament World of Composition and Communication -- Proposition 1: Ancient Near Eastern societies were hearing-dominant and had nothing comparable to authors and books as we know them -- Proposition 2: Expansions and revisions were possible as documents were copied generation after generation and eventually compiled into literary works -- Proposition 3: Effective communication must accommodate to the culture and nature of the audience -- Proposition 4: The Bible contains no new revelation about the workings and understanding of the material world -- Stepping Back and Summing Up: How the composition of the Old Testament may be understood differently in light of what is known of ancient literary culture -- Part 2. The New Testament World of Composition and Communication -- Proposition 5: Much of the literature of the Greco-Roman world retained elements of a hearing-dominant culture -- Proposition 6: Oral and written approaches to literature entail significant differences -- Proposition 7: Greek historians, philosophers, and Jewish rabbis offer instructive examples of ancient oral culture -- Proposition 8: Jesus' world was predominantly non-literate and oral -- Proposition 9: Logos/Word referred to oral communication, not to written texts -- Proposition 10: Jesus proclaimed truth in oral forms and commissioned his followers to do the same -- Proposition 11: Variants were common in the oral texts of Jesus' words and deeds -- Proposition 12: Throughout the New Testament the primary focus was on spoken rather than written words -- Proposition 13: Exact wording was not necessary to preserve and transmit reliable representations of inspired truth -- Stepping Back and Summing Up: How the composition of the New Testament may be understood differently in light of what is known of ancient literary culture -- Part 3. The Biblical World of Literary Genres -- Proposition 14: The Authority of Old Testament narrative literature is more connected to revelation than to history -- Proposition 15: The authority of Old Testament legal literature is more connected to revelation than to law -- Proposition 16: The authority of Old Testament prophetic literature is more connected to revelation than to future-telling -- Proposition 17: The genres of the New Testament are more connected to orality than textuality -- Part 4. Concluding Affirmations on the Origin and Authority of Scripture -- Proposition 18: Scripture confirms its fundamental oral nature -- Proposition 19: Scripture asserts its divine source and illocution -- Proposition 20: Inerrancy has its strengths and weaknesses -- Proposition 21: Belief in authority not only involves what the Bible is but also what we do with it -- Faithful Conclusions for Virtuous Readers
Includes bibliographical references and indexes.
Keywords: Bible -- Evidences, authority, etc; Bible and tradition; Oral communication; Oral tradition; Transmission of texts; Bibel; 2; Kommunikation; Literatur; 2; Textgeschichte; Alter Orient; Bible; Authority -- Religious aspects; Bible and tradition; Oral communication; Oral tradition; Transmission of texts; Bible / Evidences, authority, etc